Materiali Ceramici per Edilizia con Funzionalità Fotocatalitica - Tobaldi, David - Maria <1975> (Alma Mater Studiorum - Università di Bologna, 2009)
This thesis wad aimed at the study and application of titanium dioxide photocatalytic activity on ceramic materials. As a matter of fact, photocatalysis is a very promising method to face most of the problems connected with the increasing environmental pollution. Furthermore, titanium dioxide, in its anatase crystallographic phase, is one of the most investigated photocatalytic material and results to be perfectly compatible with silicate body mixes. That goal was pursued by two different strategies: 1. the addition to a body mix used for heavy clay products of several titania powders, with different mean crystallite size, surface area, morphology and anatase/rutile ratio and a titania nanosuspension as well. The titania addition followed two procedures: bulk and spray addition over the ceramic samples surface. Titania was added in two different percentages: 2.5 and 7.5 wt.% in both of the methods. The ceramic samples were then fired at three maximum temperatures: 900, 950 and 1000 °C. Afterwards, the photocatalytic activity of the prepared ceramic samples was evaluated by following the degradation of an organic compound in aqueous medium, under UV radiation. The influence of titania morphological characteristics on the photoactivity of the fired materials was studied by means of XRD and SEM observations. The ceramic samples, sprayed with a slip containing 7.5 wt.% of titania powder and fired at 900 °C, have the best photoactivity, with a complete photo-decomposition of the organic compound. At 1000 °C no sample acted as a photocatalyst due to the anatase-to-rutile phase transformation and to the reaction between titania and calcium and iron oxides in the raw materials. 2. The second one foresaw the synthesis of TiO2-SiO2 solid solutions, using the following stoichiometry: Ti1-xSixO2 where x = 0, 0.1, 0.3 and 0.5 atoms per formula unit (apfu). The mixtures were then fired following two thermal cycles, each with three maximum temperatures. The effect of SiO2 addition into the TiO2 crystal structure and, consequently, on its photocatalytic activity when fired at high temperature, was thoroughly investigated by means of XRD, XPS, FE-SEM, TEM and BET analysis. The photoactivity of the prepared powders was assessed both in gas and liquid phase. Subsequently, the TiO2-SiO2 solid solutions, previously fired at 900 °C, were sprayed over the ceramic samples surface in the percentage of 7.5 wt.%. The prepared ceramic samples were fired at 900 and 1000 °C. The photocatalytic activity of the ceramic samples was evaluated in liquid phase. Unfortunately, that samples did not show any appreciable photoactivity. In fact, samples fired at 900 °C showed a pretty low photoactivity, while the one fired at 1000 °C showed no photoactivity at all. This was explained by the excessive coarsening of titania particles. To summarise, titania particle size, more than its crystalline phase, seems to have a relevant role in the photocatalytic activity of the ceramic samples.